Preparation method and application of high-strength low-deformation nylon 66 composite material

By mixing chopped carbon fibers with TPEE resin and modifying PA66 resin, high-strength, low-deformation nylon 66 composite materials were prepared, which solved the problems of thermoplastic carbon plates in the prior art in processing and use, and achieved high material Strength, low deformation, low water absorption and good processing performance.

CN119490746APending Publication Date: 2025-02-21FUJIAN YONGJUXING NEW PLASTIC MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411762086.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing thermoplastic carbon plates for shoes are prone to material during processing, and the interface force between carbon fiber and PA66 composite materials is not strong, resulting in a decrease in strength, easy to break or white, and PA66 is easy to absorb water, affecting the long-term use of the product and the stability of the dimensions. sex.

Method used

Modified chopped carbon fiber and TPEE resin are mixed, and melt-extruded and granulated by a intensive extrusion machine. Then PA66 resin, organic flake silica, crosslinking agent and antioxidant are added, and the twin screws are used. The extruder carried out further processing to prepare a high-strength, low-deforming nylon 66 composite material.

Benefits of technology

The excellent mechanical properties, good bending resistance, low water absorption and good dimensional stability of the composite material are achieved, and the material explosion phenomenon is avoided during the processing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength low-deformation nylon 66 composite material. The preparation method comprises the following steps: treating the surfaces of short carbon fibers by adopting a dopamine hydrochloride solution and a surface modifier to obtain modified short carbon fibers; then compounding the modified short carbon fiber with a thermoplastic polyester elastomer (TPEE) to prepare a TPEE-carbon fiber compound; finally, nylon 66, the TPEE-carbon fiber compound, organic flaky silica, a cross-linking agent, an antioxidant and white oil are subjected to melt extrusion granulation, and the high-strength low-deformation nylon 66 composite material is prepared. The high-strength low-deformation nylon 66 composite material has the advantages of excellent mechanical property, good dimensional stability, excellent processing capacity and the like, and the invention also discloses application of the high-strength low-deformation nylon 66 composite material which is a nylon 66 composite material capable of being applied to preparation of thermoplastic carbon plates for shoes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a preparation method and application of a high-strength and low-deformation nylon 66 composite material. Background Art

[0002] Thermoplastic carbon plates for shoes have the advantages of light weight and high strength, and have developed into the preferred material in the field of modern sports shoes. Thermoplastic carbon plates can not only provide stable support for shoe materials, but are also environmentally friendly and recyclable, which meets the pursuit of sustainable development by modern consumers. In addition, thermoplastic carbon plates also show good dynamic flexibility, adapting to various sports changes of athletes' feet, and ensuring comfort and safety during exercise.

[0003] Polyamide 66 (PA66) is a common engineering plastic with good mechanical strength, plasticity, wear resistance and self-lubricating properties. It is often used as a substrate and composited with carbon fiber to make carbon plates for shoes. However, there are the following problems in the actual preparation and application process: First, during the processing, high-content carbon fiber filling is prone to cause material overflow, affecting the processing and preparation process; second, during the composite process of carbon fiber and PA66, the strength of the composite material decreases due to weak interface force or uneven dispersion, which easily causes the carbon plate to break or turn white during bending; third, PA66 has a large number of amide structures, which are very easy to absorb water and cause increased water absorption, which is not conducive to the long-term use of the product. Under normal circumstances, a water absorption rate of ≤0.5% is conducive to the long-term use of the product; fourth, PA66 is a crystalline polymer. During the molding process, the material is prone to internal stress concentration due to the activity of molecular chain segments, resulting in deformation and reduced dimensional stability. Under normal circumstances, a shrinkage rate of ≤0.5% is conducive to the dimensional stability of the product.

[0004] Therefore, developing a nylon 66 composite material with high strength and low deformation has important economic value and practical significance for improving the use effect and life of thermoplastic carbon plates for shoes. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a high-strength and low-deformation nylon 66 composite material having excellent mechanical properties, good dimensional stability and outstanding processing capability.

[0006] Another object of the present invention is to provide a nylon 66 composite material that can be used to prepare thermoplastic carbon plates for shoes.

[0007] In order to achieve the above object, the solution of the present invention is: A method for preparing a high-strength and low-deformation nylon 66 composite material comprises the following steps: Step 1: Soak 1-3 cm long chopped carbon fibers in anhydrous ethanol for 0.5-2 hours, then wash and dry with deionized water, place in a 1.5-3 g / L dopamine hydrochloride solution and stir at room temperature for 2-4 hours, then add a surface modifier, stir at 40-70 ° C for 2-4 hours, wash and dry with deionized water to obtain modified chopped carbon fibers; Step 2: Mix the modified chopped carbon fiber obtained in step 1 with TPEE resin and perform melt extrusion granulation through a banburying extruder at an extrusion temperature of 150-220° C. to obtain a TPEE-carbon fiber composite; Step 3: 40 wt%~55 wt% PA66 resin, 35 wt%~50 wt% TPEE-carbon fiber composite, 5 wt%~10 wt% organic flaky silica, 1 wt%~2 wt% cross-linking agent, 0.2 wt%~1 wt% antioxidant and 0.2 wt%~0.5wt% white oil are melt-extruded and granulated through a twin-screw extruder at an extrusion temperature of 220~270°C to obtain a high-strength and low-deformation nylon 66 composite material.

[0008] Furthermore, in step 1, the mass ratio of the chopped carbon fiber to the dopamine hydrochloride solution is 0.4-0.6:1.

[0009] Further, in step 1, the surface modifier is ethylene glycol diglycidyl ether and / or 1,4-butanediol diglycidyl ether; The mass ratio of the surface modifier to the dopamine hydrochloride solution is 0.01-0.03:1.

[0010] Furthermore, in step 2, the mass ratio of the modified chopped carbon fiber to the TPEE resin is 1-2:1.

[0011] Furthermore, in step 3, the diameter-to-thickness ratio of the organized flaky silica is 50-100:1.

[0012] Furthermore, in step 3, the cross-linking agent is at least one of epoxy chain extender ADR4468, terminal epoxy silicone oil and styrene-methyl methacrylate-glycidyl methacrylate KL-E4370.

[0013] Furthermore, in step 3, the antioxidant is at least one of antioxidant 1010, antioxidant 1076 and antioxidant 168.

[0014] Furthermore, in step 1, the pH value of the dopamine hydrochloride solution is 8.5.

[0015] An application of a high-strength, low-deformation nylon 66 composite material. The high-strength, low-deformation nylon 66 composite material is prepared by the preparation method, and the high-strength, low-deformation nylon 66 composite material is applied to the production of thermoplastic carbon plates for shoes.

[0016] After adopting the above technical scheme, the preparation method of a high-strength and low-deformation nylon 66 composite material of the present invention has the following advantages: (1) Excellent mechanical properties. PA66 is modified with TPEE-carbon fiber composite, organic flaky silica and crosslinking agent, which not only improves the dispersion of carbon fiber in the matrix resin, but also enhances the interface between the multiphases, achieving multiple improvements in the strength, modulus and toughness of the composite material (tensile strength is not less than 217MPa, basically maintained at 217~226MPa; elastic modulus is not less than 12699MPa, basically maintained at 12699~13248MPa; notched impact strength is not less than 20.8kJ·m 2 , basically maintained at 20.8~23.2kJ·m 2 ).

[0017] (2) Good bending resistance. On the one hand, the surface of the modified carbon fiber has reactive groups, which can achieve good compounding with the elastomer TPEE, which is conducive to stress transfer; on the other hand, the introduction of a cross-linking agent can improve the interface between the TPEE-carbon fiber composite and the matrix resin PA66. Under the combined effect, the composite material has good bending resistance, so that the product will not break or crack after 20,000 bends.

[0018] (3) Low water absorption and good dimensional stability. On the one hand, the organic flaky silica has good hydrophobicity, and its flaky structure can form a dense hydrophobic layer in the matrix to reduce the water absorption of the composite material; on the other hand, by introducing a crosslinking agent to form a certain crosslinking reaction with the PA66 resin, the original linear structure is changed, the steric hindrance is increased, and the hygroscopic effect of the amide structure is inhibited. Under the combined effect, the water absorption of the composite material is reduced (the water absorption rate is not higher than 0.5%, basically maintained at 0.3~0.5%). At the same time, the organic flaky silica has excellent thermal stability, and the molecular chain caused by the crosslinking effect of the crosslinking agent changes from a linear to a network structure, giving the composite material good dimensional stability (shrinkage is not higher than 0.5%, basically maintained at 0.2~0.5%). (4) Excellent processing ability. Premixing carbon fiber with TPEE effectively solves the strong hindrance of carbon fiber during extrusion; at the same time, the flaky silica has a certain lubricity, which can improve the processing fluidity of the melt, giving the composite material excellent processing ability, so that no material overflow occurs during processing. DETAILED DESCRIPTION

[0019] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments.

[0020] 1. Material preparation Example 1 A method for preparing a high-strength and low-deformation nylon 66 composite material comprises the following steps: Step 1: Soak 3 cm long chopped carbon fibers in anhydrous ethanol for 0.5 hours, then wash and dry with deionized water, put into 2 g / L dopamine hydrochloride solution (pH = 8.5, the mass ratio of chopped carbon fibers to dopamine hydrochloride solution is 0.5:1) and stir at room temperature for 4 hours, then add ethylene glycol diglycidyl ether (the mass ratio of ethylene glycol diglycidyl ether to dopamine hydrochloride solution is 0.03:1) and stir at 70 ° C for 2 hours, wash with deionized water and dry to obtain modified chopped carbon fibers; Step 2: The modified chopped carbon fiber obtained in step 1 is mixed with TPEE resin (the mass ratio of modified chopped carbon fiber to TPEE is 2:1) and melt-extruded and granulated through a banburying extruder at extrusion temperatures of 150°C, 175°C, 215°C, 220°C, 218°C, and 215°C to obtain a TPEE-carbon fiber composite; Step 3: 50 wt% PA66 resin, 42 wt% TPEE-carbon fiber composite, 6 wt% organic flaky silica (diameter-thickness ratio 50:1), 1.2 wt% ADR4468, 0.3 wt% antioxidant 168 and 0.5 wt% white oil are melt-extruded and granulated through a twin-screw extruder at extrusion temperatures of 220°C, 245°C, 268°C, 270°C, 267°C and 265°C to obtain a high-strength and low-deformation nylon 66 composite material.

[0021] Example 2 A method for preparing a high-strength and low-deformation nylon 66 composite material comprises the following steps: Step 1: Soak 1 cm long chopped carbon fiber in anhydrous ethanol for 2 hours, then wash and dry with deionized water, put it into 3 g / L dopamine hydrochloride solution (pH = 8.5, the mass ratio of chopped carbon fiber to dopamine hydrochloride solution is 0.4:1) and stir it at room temperature for 2 hours, then add 1,4-butanediol diglycidyl ether (the mass ratio of 1,4-butanediol diglycidyl ether to dopamine hydrochloride solution is 0.01:1) and stir it at 40 ° C for 4 hours, wash with deionized water and dry it to obtain modified chopped carbon fiber; Step 2: The modified chopped carbon fiber and TPEE resin (the mass ratio of modified chopped carbon fiber to TPEE is 1:1) are mixed and melt-extruded and granulated through a banburying extruder at extrusion temperatures of 150°C, 178°C, 213°C, 217°C, 220°C, and 216°C to obtain a TPEE-carbon fiber composite; Step 3: 40 wt% PA66 resin, 50 wt% TPEE-carbon fiber composite, 7 wt% organic flaky silica (diameter-thickness ratio 100:1), 2wt% KL-E4370, 0.5 wt% antioxidant 1010 and 0.5 wt% white oil are melt-extruded and granulated through a twin-screw extruder at extrusion temperatures of 220°C, 248°C, 266°C, 269°C, 270°C and 266°C to obtain a high-strength and low-deformation nylon 66 composite material.

[0022] Example 3 A method for preparing a high-strength and low-deformation nylon 66 composite material comprises the following steps: Step 1: Soak 2.5 cm long chopped carbon fibers in anhydrous ethanol for 2 hours, then wash and dry with deionized water, put into 1.5 g / L dopamine hydrochloride solution (pH = 8.5, the mass ratio of chopped carbon fibers to dopamine hydrochloride solution is 0.6:1) and stir at room temperature for 3 hours, then add 1,4-butanediol diglycidyl ether (the mass ratio of 1,4-butanediol diglycidyl ether to dopamine hydrochloride solution is 0.02:1) and stir at 65 ° C for 2 hours, wash with deionized water and dry to obtain modified chopped carbon fibers; Step 2: The modified chopped carbon fiber and TPEE resin (the mass ratio of modified chopped carbon fiber to TPEE is 1.6:1) are mixed and melt-extruded and granulated through a banburying extruder at extrusion temperatures of 150°C, 173°C, 216°C, 220°C, 218°C, and 215°C to obtain a TPEE-carbon fiber composite; Step 3: 52 wt% PA66 resin, 35 wt% TPEE-carbon fiber composite, 10 wt% organic flaky silica (diameter-thickness ratio 80:1), 1.7 wt% terminal epoxy silicone oil, 1 wt% antioxidant 1076 and 0.3 wt% white oil are melt-extruded and granulated through a twin-screw extruder at extrusion temperatures of 220°C, 242°C, 265°C, 270°C, 270°C, and 265°C to obtain a high-strength and low-deformation nylon 66 composite material.

[0023] Comparative Example 1 In this comparative example, PA66, antioxidant 168 and white oil are directly melt-extruded and granulated through a twin-screw extruder at extrusion temperatures of 220° C., 245° C., 268° C., 270° C., 267° C. and 265° C. to obtain PA66 material.

[0024] Comparative Example 2 The difference from Example 1 is that this comparative example does not add TPEE-carbon fiber composite, and the components are 92 wt% PA66 resin, 6 wt% organic flaky silica (diameter-thickness ratio 50:1), 1.2 wt% ADR4468, 0.3 wt% antioxidant 168, and 0.5 wt% white oil. The extrusion temperatures are 220°C, 245°C, 268°C, 270°C, 267°C, and 265°C to obtain PA66 composite materials.

[0025] Comparative Example 3 The difference from Example 1 is that the chopped carbon fibers in this comparative example are not subjected to the surface modification treatment in step 1, and other operations and proportions remain unchanged. The extrusion temperatures are 220°C, 245°C, 268°C, 270°C, 267°C, and 265°C to obtain a PA66 composite material.

[0026] Comparative Example 4 The difference from Example 1 is that the modified chopped carbon fiber in this comparative example does not undergo the composite treatment in step 2, and is obtained by a single addition with other operations and proportions unchanged, and the extrusion temperatures are 220°C, 245°C, 268°C, 270°C, 267°C, and 265°C to obtain a PA66 composite material.

[0027] Comparative Example 5 The difference from Example 1 is that this comparative example does not add organized flaky silica, and the components are 56 wt% PA66 resin, 42 wt% TPEE-carbon fiber composite, 1.2 wt% ADR4468, 0.3 wt% antioxidant 168, and 0.5 wt% white oil. The extrusion temperatures are 220°C, 245°C, 268°C, 270°C, 267°C, and 265°C to obtain a PA66 composite material.

[0028] Comparative Example 6 The difference from Example 1 is that no cross-linking agent is added in this comparative example, and the components are 51.2 wt% PA66 resin, 42 wt% TPEE-carbon fiber composite, 6 wt% organic flaky silica (diameter-thickness ratio 50:1), 0.3 wt% antioxidant 168, and 0.5 wt% white oil. The extrusion temperatures are 220°C, 245°C, 268°C, 270°C, 267°C, and 265°C to obtain a PA66 composite material.

[0029] Comparative Example 7 The difference from Example 1 is that in this comparative example, the diameter-to-thickness ratio of the organic flaky silica is 30:1, and the rest remains unchanged. The extrusion temperatures are 220°C, 245°C, 268°C, 270°C, 267°C, and 265°C to obtain a PA66 composite material.

[0030] 2. Performance Test The nylon 66 composite materials prepared in each embodiment and comparative example were made into test specimens according to the following relevant performance standards, and the tensile strength (ISO 527-1 / 2), elastic modulus (ISO 178 / 2010), notched impact strength (ISO 180 / 2001), bending resistance (GB / T 3903.1-2017), water absorption (GB / T 1034-2008) and shrinkage (GB / T 17037.4-2003) of the nylon 66 composite materials were measured. At the same time, the material bubbling during the processing was observed. The results are shown in Table 1.

[0031] Table 1 Performance test data of nylon 66 composite materials

[0032] It can be seen from the data in Table 1 that the high-strength and low-deformation nylon 66 composite materials prepared in Examples 1 to 3 have excellent performance. The tensile strength of the material is not less than 217 MPa, basically maintained at 217-226 MPa; the elastic modulus is not less than 12699 MPa, basically maintained at 12699-13248 MPa; the notched impact strength is not less than 20.8 kJ·m 2 , basically maintained at 20.8~23.2kJ·m 2 The water absorption rate is not higher than 0.5%, and basically maintained at 0.3~0.5%. The shrinkage rate is not higher than 0.5%, and basically maintained at 0.2~0.5%. The product did not break or turn white in the 20,000 bending tests, and the material can be cut normally during the processing without any overflow.

[0033] It can be found from Comparative Example 1 that nylon 66 material has the disadvantages of low strength, high water absorption, large shrinkage and poor bending ability, and is difficult to be used as a thermoplastic carbon plate for shoes. By modifying the nylon 66 material, the above disadvantages are effectively overcome, as shown in Examples 1 to 3 in Table 1. Compared with Example 1, in the case of lack of TPEE-carbon fiber composite, the mechanical properties of the material in Comparative Example 2 are significantly reduced, the water absorption and shrinkage of the material are significantly increased, and there is a phenomenon of bending and whitening; in the case of lack of surface treatment of the chopped carbon fiber in Comparative Example 3, the mechanical strength of the material is reduced, the water absorption and shrinkage of the material are increased, and there is a phenomenon of bending and whitening; in the case of modified chopped carbon fiber in Comparative Example 4 without compounding with TPEE, the mechanical strength of the material is reduced, the water absorption and shrinkage of the material are increased, and there are phenomena of bending, whitening and material bubbling; in the case of not adding organic flaky silica in Comparative Example 5, the mechanical strength of the material is reduced, the water absorption and shrinkage of the material are increased, and there is a partial phenomenon of material bubbling; in the case of not adding a cross-linking agent in Comparative Example 6, the mechanical strength of the material is reduced, and the water absorption and shrinkage of the material are increased; in Comparative Example 7, under the condition of a lower diameter-to-thickness ratio of the organic flaky silica, the strength of the material is reduced, the shrinkage of the material is significantly increased, and it fails to meet the application requirements.

[0034] After adopting the above technical scheme, the preparation method of a high-strength and low-deformation nylon 66 composite material of the present invention has the following advantages: (1) Excellent mechanical properties. PA66 is modified with TPEE-carbon fiber composite, organic flaky silica and crosslinking agent, which not only improves the dispersion of carbon fiber in the matrix resin, but also enhances the interface between the multiphases, achieving multiple improvements in the strength, modulus and toughness of the composite material (tensile strength is not less than 217MPa, basically maintained at 217~226MPa; elastic modulus is not less than 13699MPa, basically maintained at 13699~14248MPa; notched impact strength is not less than 20.8kJ·m 2 , basically maintained at 20.8~23.2kJ·m 2 ).

[0035] (2) Good bending resistance. On the one hand, the surface of the modified carbon fiber has reactive groups, which can achieve good compounding with the elastomer TPEE, which is conducive to stress transfer; on the other hand, the introduction of a cross-linking agent can improve the interface between the TPEE-carbon fiber composite and the matrix resin PA66. Under the combined effect, the composite material has good bending resistance, so that the product will not break or crack after 20,000 bends.

[0036] (3) Low water absorption and good dimensional stability. On the one hand, the organic flaky silica has good hydrophobicity, and its flaky structure can form a dense hydrophobic layer in the matrix to reduce the water absorption of the composite material; on the other hand, by introducing a cross-linking agent to form a certain cross-linking reaction with the PA66 resin, the original linear structure is changed, the steric hindrance is increased, and the hygroscopic effect of the amide structure is inhibited. Under the combined effect, the water absorption of the composite material is reduced (the water absorption rate is not higher than 0.5%, basically maintained at 0.3~0.5%). At the same time, the organic flaky silica has excellent thermal stability, and the cross-linking effect of the cross-linking agent causes the molecular chain to change from a linear to a network structure, which gives the composite material good dimensional stability (the shrinkage rate is not higher than 0.5%, basically maintained at 0.2~0.5%).

[0037] (4) Excellent processing capability. Premixing carbon fiber with TPEE effectively solves the strong resistance of carbon fiber during extrusion. At the same time, silica with a flaky structure has a certain lubricity, which can improve the processing fluidity of the melt, giving the composite material excellent processing capability, so that no material overflow occurs during the processing.

[0038] In view of the fact that the specially prepared high-strength and low-deformation nylon 66 composite material of the present invention has the above-mentioned excellent properties, it is particularly suitable for the production of thermoplastic carbon plates for shoes.

[0039] The above embodiments do not limit the preparation method of the present invention, and any appropriate changes or modifications made thereto by ordinary technicians in the relevant technical field should be deemed to be within the patent scope of the present invention.

Claims

1. A method for preparing a high-strength and low-deformation nylon 66 composite material, characterized in that: The following steps are involved: Step 1: Soak 1-3 cm long chopped carbon fibers in anhydrous ethanol for 0.5-2 hours, then wash and dry with deionized water, place in a 1.5-3 g / L dopamine hydrochloride solution and stir at room temperature for 2-4 hours, then add a surface modifier, stir at 40-70 ° C for 2-4 hours, wash and dry with deionized water to obtain modified chopped carbon fibers; Step 2: Mix the modified chopped carbon fiber obtained in step 1 with TPEE resin and perform melt extrusion granulation through a banburying extruder at an extrusion temperature of 150-220° C. to obtain a TPEE-carbon fiber composite; Step 3: 40 wt%~55 wt% PA66 resin, 35 wt%~50 wt% TPEE-carbon fiber composite, 5 wt%~10wt% organic flaky silica, 1 wt%~2 wt% cross-linking agent, 0.2 wt%~1 wt% antioxidant and 0.2 wt%~0.5 wt% white oil are melt-extruded and granulated through a twin-screw extruder at an extrusion temperature of 220~270°C to obtain a high-strength and low-deformation nylon 66 composite material.

2. The method for preparing a high-strength and low-deformation nylon 66 composite material according to claim 1, characterized in that: In step 1, the mass ratio of the chopped carbon fibers to the dopamine hydrochloride solution is 0.4-0.6:

1.

3. The method for preparing a high-strength and low-deformation nylon 66 composite material according to claim 1, characterized in that: In step 1, the surface modifier is ethylene glycol diglycidyl ether and / or 1,4-butanediol diglycidyl ether; The mass ratio of the surface modifier to the dopamine hydrochloride solution is 0.01-0.03:

1.

4. The method for preparing a high-strength and low-deformation nylon 66 composite material according to claim 1, characterized in that: In step 2, the mass ratio of the modified chopped carbon fiber to the TPEE resin is 1-2:

1.

5. The method for preparing a high-strength and low-deformation nylon 66 composite material according to claim 1, characterized in that: In step 3, the diameter-to-thickness ratio of the organized flaky silica is 50-100:

1.

6. The method for preparing a high-strength and low-deformation nylon 66 composite material according to claim 1, characterized in that: In step 3, the cross-linking agent is at least one of epoxy chain extender ADR4468, terminal epoxy silicone oil and styrene-methyl methacrylate-glycidyl methacrylate KL-E4370.

7. The method for preparing a high-strength and low-deformation nylon 66 composite material according to claim 1, characterized in that: In step 3, the antioxidant is at least one of antioxidant 1010, antioxidant 1076 and antioxidant 168.

8. The method for preparing a high-strength and low-deformation nylon 66 composite material according to claim 1, characterized in that: In step 1, the pH value of the dopamine hydrochloride solution is 8.

5.

9. An application of a high-strength and low-deformation nylon 66 composite material, characterized in that: The high-strength and low-deformation nylon 66 composite material is prepared by the preparation method described in any one of claims 1 to 8, and the high-strength and low-deformation nylon 66 composite material is used in the production of thermoplastic carbon plates for shoes.